(untitled) (Educational Knowledge, 2021)
Life skills are considered adaptive and positive behavior skills that enable individuals to effectively meet the demands and challenges of daily life. These include self-awareness, empathy, interpersonal relationships, decision-making, problem-solving and conflict resolution, assertiveness, creative thinking, critical thinking, emotional and emotional regulation, and stress management. These skills are distributed across three areas: social, emotional, and cognitive. Furthermore, their influence can be found in the way content is taught, instructed, and developed within higher education institutions, specifically for students in teacher training programs for early childhood and preschool education. This article presents the results of a mixed-methods study, with a descriptive-correlational quantitative phase and a phenomenological qualitative phase. This design made it possible to obtain a comprehensive analysis of life skills and their incorporation into the curriculum design of the teacher training and undergraduate degree programs in Early Childhood and Preschool Education in El Salvador.